Synaptic alterations in the rTg4510 mouse model of tauopathy. Issue 6 (20th February 2013) - Kopeikina, Katherine J.; Polydoro, Manuela; Tai, Hwan‐Ching; Yaeger, Erich; Carlson, George A.; Pitstick, Rose; Hyman, Bradley T.; Spires‐Jones, Tara L.
Abstract Synapse loss, rather than the hallmark amyloid‐β (Aβ) plaques or tau‐filled neurofibrillary tangles (NFT), is considered the most predictive pathological feature associated with cognitive status in the Alzheimer's disease (AD) brain. The role of Aβ in synapse loss is well established, but despite data linking tau to synaptic function, the role of tau in synapse loss remains largely undetermined. Here we test the hypothesis that human mutant P301L tau overexpression in a mouse model (rTg4510) will lead to age‐dependent synaptic loss and dysfunction. Using array tomography and two methods of quantification (automated, threshold‐based counting and a manual stereology‐based technique) we demonstrate that overall synapse density is maintained in the neuropil, implicating synapse loss commensurate with the cortical atrophy known to occur in this model. Multiphoton in vivo imaging reveals close to 30% loss of apical dendritic spines of individual pyramidal neurons, suggesting these cells may be particularly vulnerable to tau‐induced degeneration. Postmortem, we confirm the presence of tau in dendritic spines of rTg4510‐YFP mouse brain by array tomography. These data implicate tau‐induced loss of a subset of synapses that may be accompanied by compensatory increases in other synaptic subtypes, thereby preserving overall synapse density. Biochemical fractionation of synaptosomes from rTg4510 brain demonstrates a significant decrease in expression of several synaptic proteins, suggesting a functional deficit of remaining synapses in the rTg4510 brain. Together, these data show morphological and biochemical synaptic consequences in response to tau overexpression in the rTg4510 mouse model. J. Comp. Neurol., 521:1334–1353, 2013. © 2012 Wiley Periodicals, Inc.